FORMULASI DAN UJI EFEKTIVITAS SEDIAAN GEL EKSTRAK DAUN BAJAKAH KALALAWIT (Uncaria gambir Roxb.) TERHADAP PROSES PENYEMBUHAN LUKA BAKAR PADA MENCIT PUTIH - Ayuchecaria, Noverda; Yohanes Edy Gunawan; Efriyana Oksal; Shesanthi Citrariana (Jurnal Insan Farmasi Indonesia, 2023)
Burns are tissue loss caused by contact with heat sources. Burns will not only cause skin damage, but also affect the entire body system. Bajakah kalalawit contains polyphenolic compounds. This research aims to design a gel preparation formulation that is effective in the healing process of burn wounds in white mice. The preparation was also tested for its physicochemical characteristics including organoleptic test, homogeneity test, pH test, spreadability and stickiness test and irritation test. The results showed that all formulas were homogeneous and no organoleptic changes occurred after 14 days. The pH range of Bajakah gel is 6.16 – 7.46 which meets the skin's pH requirements. The diameter range of spreading power is between 5-7 cm. The adhesion power of formulas 2 and 3 meets the requirements (<4 seconds). The four formulas did not show irritation in the irritation test. The conclusion of this research is that Bajakah kalalawite extract gel with the composition of Formulas 2 and 3 meets the requirements for physical quality characteristic tests including organoleptic, homogeneity, pH, spreadability, adhesive power and irritation test. The diameter of the burn wound showed that there was a significant difference in treatment compared to the negative control group (p<5%).